Working Students in Higher Education: Challenges and Solutions - Tumin Tumin; Ahmad Faizuddin; Firman Mansir; Halim Purnomo; Nurul Aisyah (Al-Hayat Al-Istiqomah Foundation, 2020)
The current study explores the experiences of working students, especially in higher learning institutions in coping with the challenges of working while studying. It is expected that the suggestions and recommendations from the study can improve working students’ experiences to be successful in both working and studying. This qualitative research investigates the experiences of working students at the International Islamic University Malaysia. Some working students were purposively chosen and interviewed to know the challenges they faced and how they overcome the problems. The findings of the current study show that the informants fully understood the concept of working while studying and considered it as a financial necessity and self-improvement. The informants exposed several challenges of working students such as time constraints and commitment to their studies. Despite the challenges, the informants considered working while studying as a motivation to further develop themselves and acquire necessary skills for better employment. This study is important as many college students are working while enrolled in higher education. They may experience time constraints managing the responsibilities of both student and worker. Thus, it is significant to understand their experiences that may affect the future of their academic studies. This study provides some implications and recommendations for working students to overcome the challenges. They include time management, commitment, discipline, and responsibility.